Research on Seismic Performance of 735 MPa High-Strength Reinforced Concrete Frame Joints - Xiao Zhang; Fei Han; Xuekun Wang; Lele Sun; Qi Wang; Peijun Wang (Buildings, 2023)
To study the seismic performance of high-strength reinforced concrete frame joints, cyclic loading tests were carried out on six concrete beam-column joints configured with the new Cold-rolled Ribbed Bar (CRB) 735 high-strength steel reinforcement and one joint with Hot-rolled Ribbed Bar (HRB) 400 ordinary steel reinforcement to obtain the effects of the axial compression ratio and the stirrup ratio in the joint core on the seismic performance of the joints. The test results show that the following: (1) Increasing the axial compression ratio can improve the energy dissipation characteristics of the joints configured with CRB735, but cannot effectively improve the ultimate shear capacity of the joints. Larger axial compression ratio will cause earlier cracks in the core area and reduce the ductility of the specimens by 6.1~27.9%. (2) Increasing the stirrup ratio in the joint core will increase the shear capacity of the joint by 5.3~8.1% while also increasing the failure displacement by 2.8~14.9%. (3) When the joints are configured with CRB735 stirrups, the rate of stiffness degradation from core cracking to the yielding stage of the specimens will be effectively delayed. (4) Compared with the joint configured with HRB400, the ultimate loading process of the joints using CRB735 is shorter, the yield load and yield displacement are higher, and the specimens are close to the ultimate state when they reach yield. Finally, the shear capacity of concrete beam-column joints configured with CRB735 can be calculated using the relevant shear capacity equation in GB50010-2010 Code for Design of Concrete Structures, and has a certain safety reserve. In the equation, the yield strength of CRB735 steel reinforcement is recommended to be 735 MPa.